Symposium on Surface and subsurface reconnaissance. Presented at the fifty-fourth annual meeting, American Society for Testing Materials - Symposium on Surface and Subsurfce reconnaisance. Prensented at the Fifty-fourth Annual Meeting, American Society for Testing Materials (June 19, 1951 : Arlantic City, NJ); American Society for Testing Materials (Philadelphia, Pa. : American Society for Testing Mateials, 1952)
09